The impact of obesity and hypercaloric diet consumption on anxiety and emotional behavior across the lifespan. (December 2017) - Baker, Kathryn D.; Loughman, Amy; Spencer, Sarah J.; Reichelt, Amy C.
Highlights: High incidence of anxiety disorders in people with obesity. Common neurobiological mechanisms link obesity and mood disorders. We describe effects of hypercaloric diets during various neurodevelopmental periods. Increased rates of obesity in young people may promote anxiety disorder development. Abstract: Obesity is an increasing problem in young people. Childhood obesity and overweight have increased rapidly on a global scale, and have tripled in the past 30 years, to affect approximately one in five children. Diets high in refined fats and sugar are a major contributor to the development of obesity, and the effects of such obesity-inducing hypercaloric diets on brain function may contribute to the high prevalence of anxiety disorders in people with obesity. Anxiety disorders typically emerge in childhood and adolescence, and symptoms often continue into adulthood. Based on this symptomology, we consider anxiety-related behavioral consequences of hypercaloric diets across development. We review research on the effects of hypercaloric dietary manipulations across the lifespan on emotion regulation and the neurobiological mechanisms that underpin these processes. Cumulatively, the findings reveal that gestation and the juvenile/adolescent developmental periods may be early-life windows of vulnerability for developing anxiety in later life due to the augmented effects of these diets on neuroendocrine stress systems and the maturation of neural circuitry supporting emotion regulation.